2008
DOI: 10.1097/01.prs.0000297833.53794.27
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cotinine Concentration and Wound Complications in Head and Neck Reconstruction

Abstract: A serum cotinine concentration greater than 10 ng/ml may predict an increased risk of wound complication in head and neck flap reconstruction and may serve as an objective, easily measured variable with which to identify patients who may benefit from an aggressive smoking cessation program before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 34 publications
2
58
2
3
Order By: Relevance
“…This may be because, given the social stigma associated with smoking among head and neck cancer patients, 45 self-reported smoking may be less accurate than biochemically verified smoking status and might introduce misrepresentation of continuing smokers. 8,[45][46][47] However, the misrepresentation of current smokers can be minimized by repeated assessment of self-report smoking status as was done in this and another study conducted with head and neck cancer patients. 45 Several hypotheses have been proposed to explain the relationship between smoking after diagnosis and higher mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because, given the social stigma associated with smoking among head and neck cancer patients, 45 self-reported smoking may be less accurate than biochemically verified smoking status and might introduce misrepresentation of continuing smokers. 8,[45][46][47] However, the misrepresentation of current smokers can be minimized by repeated assessment of self-report smoking status as was done in this and another study conducted with head and neck cancer patients. 45 Several hypotheses have been proposed to explain the relationship between smoking after diagnosis and higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Continued smoking following diagnosis is associated with decreased response to radiotherapy and chemotherapy, impaired wound healing, increased infections and circulatory problems, and late complications (eg, severe fibrosis, dysphagia). [5][6][7][8][9][10][11] Conversely, smoking cessation after diagnosis shows several medical benefits, such as decreased fatigue and shortness of breath, increased activity level and quality of life, and improved treatment toxicity. 12,13 The 2014 Surgeon General's report "The Health Consequences of Smoking-50 Years of Progress" (SGR) acknowledged causal relationships between smoking and adverse health outcomes among cancer patients, such as increases in overall mortality, cancer-specific mortality, and second primary cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Bei Patienten mit Kopf-Hals-Tumoren, die sich einer gestielten oder frei mikrovaskulären Lappendeckung unterzogen, zeigte sich in einer prospektiven Untersuchung unter 89 Patienten mit 101 Lappenrekonstruktionen eine Verdoppelung des postoperativen Komplikationsrisikos bei präopera-tiven Cotinine-Spiegeln größer als 10 ng/ ml (relatives Risiko 1,9, 95%-Konfidenzintervall 1,1-3,3) [16].…”
unclassified
“…Jang et al, 2011 [38] 1 effects of smoking may be underestimated. For example, Marin et al [41] in 2008 demonstrated that self-reported current smoking had no significant effect on wound healing in head/neck cancer patients, but biochemically confirmed tobacco use with serum cotinine significantly predicted poor surgical outcomes. Recent studies have developed prognostic algorithms for smoking in head and neck cancer patients [42], and others have extended evidence to suggest that smoking be considered as a new standard part of cancer staging [43], which may be important considerations given the broad diversity of effects due to smoking.…”
Section: Tobacco and Cancermentioning
confidence: 99%